APPLICATION OF ACCESS CONTROL LIST FOR NETWORK SECURITY AT CISCO ROUTER AS A FIREWALL - Diky Heryanto; Salma Azizah (Jurnal PPI Dunia, 2019)
The provision limiting access to network users is one of the defensive action system from cyber attacks that can occur through a network connected to the user. Installation ACL device the router can be a firewall, where each incoming and outgoing packets will be matched with a list of existing entries, and then will proceed preconfigured actions.